Don’t Fake It, Make It! Technology and Tools for Virtual Hosts - Jarred A. Shellhouse; Lauri M. Baker; Anissa Zagonel; Phillip Stokes; Cheryl R. Boyer (EDIS)
The “Don’t Fake it, Make it!” series assists virtual conference and meeting hosts in creating an engaging program to benefit their participants. This new 6-page publication of the UF/IFAS Department of Agricultural Education and Communication gives an overview of common features hosts look for in virtual conference software platforms before committing to one. Written by Jarred A. Shellhouse, Lauri M. Baker, Anissa Zagonel, Phillip Stokes, and Cheryl R. Boyer.